Ciri Khas Pandeglang dalam Karya Seni Patung (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2021)
The creation of visual art works in the form of sculptures, this work is an expression of the artist in capturing all things related and is a characteristic of the Pandeglang area, Banten Province. Then the characteristics of the Pandeglang area combine the artists by relying on personal styles so that they become new forms and are transformed into sculptures made from paper pulp, the purpose of this amalgamation is so that the works of the artists' sculptures can be accepted and appreciated by the Pandeglang people. The rhino statue in the Pandeglang area is a source of inspiration for artists in making this sculpture, because the existence of these rhino statues is a benchmark for artists to make a sculpture that can be appreciated and even accepted by the Pandeglang community, the artist concludes the acceptance of rhino statues in Pandeglang. present because the object is a characteristic and icon of the Pandeglang area because the one- horned rhino is an endemic animal that can only be found in Pandeglang Regency.